PENGARUH KEADILAN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN DENGAN KEPUASAN KERJA KARYAWAN SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PT. MUARA MALL TERNATE) - Arsyila Humairah Albaar; Ruslan Kamis (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2022)
This study aims to determine the effect of 1) To find outwhether organizational justice has an effect on employee turnoverintention at PT Muara Mall Ternate; (2) Knowing whetherorganizational justice has an effect on job satisfaction at PT Muara MallTernate; (3) Knowing whether job satisfaction has an effect onemployee turnover intention at PT Muara Mall Ternate; and (4)Knowing whether organizational justice has an effect on turnoverintention with job satisfaction as a mediating variable at PT Muara MallTernate. The number of research samples is 71 respondents. The dataanalysis technique used in this study is SEM analysis using SmartPartial Least Square (PLS) version 3 as a statistical test tool.Methodology: The analytical model used are Structural EquationModeling with SMART PLS as tools for the statistical test. Datacollection tools used are questionnaires and interviews, and thenumber of respondents was 71 employee.Finding: H1, H2, H3, and H4 are accepted at the 5% confidence level.n other words, the t-count value of each variable is greater than the ttableat the 5% confidence level.Conclusion: Te results of this study indicate that: (1) Organizationaljustice has a positive and positive effect on turnover intention at PT.Muara Mall Ternate; (2) organizational justice has a positive influenceon job satisfaction at PT. Muara Mall Ternate; (3) Job satisfaction has apositive influence on turnover intention at PT. Muara Mall Ternate; and(4) and job satisfaction is a variable capable of mediating the effect oforganizational justice on turnover intention at PT. Muara Mall Ternate